MEMBANGUN KESADARAN PAJAK MELALUI PELATIHAN EKSLUSIF UNTUK UMKM DI KABUPATEN KUNINGAN - Suhendar, Dadang; Dwi Martika, Lia; Nurhandika, Arief; Hamzah, Amir (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
The tax awareness training for SMEs in Luragung Village, Kuningan Regency, responds to the low understanding and compliance with taxation at the local level. It was found that most SMEs lack sufficient understanding of tax obligations and the benefits of tax compliance, which impacts business development and financial health. Involving 20 SMEs from various industrial sectors, the program employs a combination of socialization, education, and training. Initial socialization covers basic understanding of taxation, while educational sessions provide in-depth insights. Evaluation through questionnaires, group discussions, and direct observations is conducted to measure program effectiveness. The results indicate an increase in awareness, tax compliance, and financial health among SMEs in Luragung Village.